The Development of Android-Based Mobile-learning Media on Virus Material to Improve Learning Outcomes in Class X Senior High School - Desi Rahmasuci; Sri Ngabekti (Journal of Biology Education, 2023)
The purpose of this study was to test the feasibility, practicality, and effectiveness of learning media using Android-based mobile learning media on virus material to improve student learning outcomes. This type of research is "research and development" with reference to the ADDIE model from the Robert Maribe Branch, namely: analysis, design, development, implementation, and evaluation. Students in classes X4 and X8 at SMA N-1 MOJOTENGAH for the 2021-2022 academic year are the focus of this study. Data collection was carried out through interviews, questionnaires, and tests. The data obtained were analyzed using a descriptive quantitative test (N-gain). The results of the study showed: 1) mobile-learning media based on android on virus material as teaching material for class X was declared valid and feasible to use; 2) android-based mobile-learning media on virus material as teaching material for class X met very practical practicality criteria; and 3) mobile-learning media based on android on virus material can improve student learning outcomes in the moderate category.